اثر الخصائص البشرية في زيادة ملوثات الهواء في محافظة القادسية - الدجيلي، علي مهدي جواد Aldjaili, Ali Mahdi Jawwad; اللهيبي، عتاب يوسف كريم Alluhaibi, Ettab Yousuf Karim (جامعة الكوفة - كلية الآداب, 2017)
That air pollution is one of the most serious problems facing the man in his daily life, which caused him great harm, especially when exceeded critical limits for air pollutants, and is dangerous air pollutants in being spread rapidly and in large quantities in the layer of the lower atmosphere (the class that lives by humans). The study shows the impact of human characteristics in the increase of air pollutants as the increase in the number of the population and increase the number of cars and their key role in the increase of air pollution, including emissions of gases and minutes working on increasing pollution, as well as industrial activity as the industry is a major source of pollution and different industries including subtract from contaminated materials from industrial production processes and what the different industries in the study area from the impact of an increase in pollutants, as well as the preparation and the quantities of waste generators in the region, where these properties are working to increase air pollutants in the study area.
ان تلوث الهواء هو عن اخطر المشاكل التي تجابه الانسان في حياته اليومية والتي تسبب له ضررا بالغاً خاصة عند تجاوزه الحدود الحرجة لملوثات الهواء، وتكمن خطورة ملوثات الهواء في كونها تنتشر بسرعة وبكميات كبيرة في طبقة الجو السلفي (الطبقة التي يعيش بها الانسان). توضح الدراسة اثر الخصائص البشرية في زيادة ملوثات الهواء حيث ان زيادة اعداد السكان وزيادة اعداد السيارات وما لها من دور اساسي وفعال في زيادة تلوث الهواء بما تطلقه من غازات ودقائق تعمل على زيادة التلوث، فضلا عن النشاط الصناعي اذ تعتبر الصناعة مصدراً رئيسياً للتلوث وتختلف الصناعات بما تطرحه من المواد الملوثة من عمليات الانتاج الصناعية وما للصناعات المختلفة في منطقة الدراسة من اثر في زيادة الملوثات، فضلا عن اعداد المولدات وكميات النفايات في المنطقة، حيث تعمل، هذه الخصائص، علي زيادة ملوثات الهواء في، منطقة الدراسة.
Keywords: تلوث الهواء; محافظة القادسية (العراق); تلوث البيئة